MnAl Layered Double Hydroxide Nanoparticles as a Dual‐Functional Platform for Magnetic Resonance Imaging and siRNA Delivery - Zuo, Huali; Chen, Weiyu; Li, Bei; Xu, Kewei; Cooper, Helen; Gu, Zi; Xu, Zhi Ping (Chemistry : a European journal, 2017)
Multifunctional nanoparticles for cancer theranosis have been widely explored for effective cancer detection and therapy. In this work, dually functionalised manganese‐based layered double hydroxide nanoparticles (Mn‐LDH) were examined as an effective anticancer drug/gene delivery system and for T1‐weighted magnetic resonance imaging (MRI) in brain cancer theranostics. Such Mn‐LDH have been shown to accommodate dsDNA/siRNAs and efficiently deliver them to Neuro‐2a cells (N2a). Mn‐LDH have also shown high biocompatibility with low cytotoxicity. Importantly, the cell‐death siRNA (CD‐siRNA) delivered with Mn‐LDH more efficiently kills brain cancer cells than the free CD‐siRNA. Moreover, Mn‐LDH can act as excellent contrast agents for MRI, with an r1 value of 4.47 mm−1 s−1, which is even higher than that of commercial contrast agents based on Gd complexes (r1=3.4 mm−1 s−1). Altogether, the high delivery efficacy and MRI contrast capability make dual‐functional Mn‐LDH potential bimodal agents for simultaneous cancer diagnosis and therapy. Multifunctional nanoparticles: Dual‐functional manganese‐based layered double hydroxide nanoparticles (Mn‐LDH) were fabricated by a co‐precipitation method. Their pH‐sensitive behaviour significantly enhanced T1‐weighted magnetic resonance imaging, which is highly beneficial for the detection of tumour cells and tissues. Anticancer therapeutics carried by Mn‐LDH more efficiently killed cancer cells than their free counterparts (see figure).